Effective Modeling of Tunable Graphene with Dispersive FDTD - GSTC Method - Xiaofeng Du,; Huan Yu,; Mengmeng Li, (Applied Computational Electromagnetics Society Journal (ACES), 2019)
We propose an effective method of dispersive finite difference time domain-generalized sheet transition conditions (FDTD-GSTCs) for the modeling of electromagnetic fields from tunable graphene with nearly zero thickness. To model the tunable graphene effectively, the susceptibilities are introduced instead of its physical structure, which can be extracted from reflection or transmission coefficients. In order to model the graphene in broadband, a dispersive FDTD-GSTC method is introduced by fitting the susceptibilities with respect to frequencies with the complex-conjugate poleresidue (CCPR) pairs. Numerical results demonstrate the validity of the proposed method.